1980
DOI: 10.1111/j.1365-2621.1980.tb07445.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hot‐boning and Cooking Method Upon Physical Changes, Cooking Time and Losses, and Tenderness of Beef Roasts

Abstract: Beef semimembranosus and semitendinosus muscles were removed prerigor (1 hr postmortem) and postrigor (7 days postmortem) to evaluate the effects of steam, hot water vat, and convectional electric cookery upon length, width, and depth changes, cooking losses, shear force values, and time required to heat product to an internal temperature of 68°C. Roasts cooked prerigor were significantly shorter and thicker than those cooked postrigor. Cooking losses were significantly lower (6.5%) with prerigor roasts. Lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…Panelists probably associated this, "grittiness" .with more connective tissue in hot-boned samples, when in fact it was probably extensive areas of supercontraction nodes produced under heat rigor. The shear force values for hot-and cold-boned roasts in our study are very similar to those found on adjacent roasts after cooking and before freezing (Ray et al, 1980). Thus, the freezing and thawing of these roasts exerted no effect on shear force values.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Panelists probably associated this, "grittiness" .with more connective tissue in hot-boned samples, when in fact it was probably extensive areas of supercontraction nodes produced under heat rigor. The shear force values for hot-and cold-boned roasts in our study are very similar to those found on adjacent roasts after cooking and before freezing (Ray et al, 1980). Thus, the freezing and thawing of these roasts exerted no effect on shear force values.…”
Section: Resultssupporting
confidence: 87%
“…(1952), Weidemann et al (1967) and Cia and Marsh (1976) have found prerigor cooked muscle to be more tender than postrigor cooked muscle. However, Ray et al (1980) and Montgomery et al (1977) reported decreased tenderness in prerigor cooked muscle.…”
Section: Introduction Energy Conservationmentioning
confidence: 86%
“…Expressing these results on a dry weight basis (d)'resulted in no significant differences, because the HB samples had a higher (PcO.05) amount of moisture than the CB samples. These results confirm findings of other researchers who found HB meat to have a higher water-holding capacity (WHC) than CB meat (Kastner and Russell, 1975;Berry et al, 1980;Corte et al, 1980;ray et al, 1980;1982;Taylor et al, 1980;Griffin et al, 1981;1982;Hamm, 1982;Motycka and Bechtel, 1983). Percentage ash in HB meat was higher (PcO.01) than in CB samples, which could result from the higher moisture retention in the HB meat and, thus, more ash particles in the beef log.…”
Section: Proximate Analysissupporting
confidence: 94%
“…A lot of research has also been conducted to improve the process, e.g. to improve water-holding capacity (WHC), to enhance emulsification capacity (Fischer et al, 1979;Honikel and Hamm, 1978;Huffman et al, 1984;Sadler and Swan, 1997) and to reduce heat loss (Ray et al, 1980). De Femery and Pool (1960) reported that storage of chicken meat at higher temperature (37)(38)(39)(40)(41) o C) immediately after slaughter can accelerate the rate of glycolysis and, then, complete rigor mortis earlier.…”
Section: Introductionmentioning
confidence: 99%